A novel compound, denosomin, ameliorates spinal cord injury via axonal growth associated with astrocyte‐secreted vimentin. (24th January 2013) - Teshigawara, Kiyoshi; Kuboyama, Tomoharu; Shigyo, Michiko; Nagata, Aiko; Sugimoto, Kenji; Matsuya, Yuji; Tohda, Chihiro
Abstract : Background and Purpose: In the spinal cord injury (SCI) axon regeneration is inhibited by the glial scar, which contains reactive astrocytes that secrete inhibitory chondroitin sulphate proteoglycan (CSPG). We previously reported that a novel compound, denosomin, promotes axonal growth under degenerative conditions in cultured cortical neurons. In this study, we investigated the effects of denosomin on functional recovery in SCI mice and elucidated the mechanism though which denosomin induces axonal growth in the injured spinal cord. Experimental Approach: Denosomin was administered p.o. for 7 or 14 days to contusion mice. Behavioural evaluations and immunohistochemistry were done. Primary cultured cortical neurons and astrocytes were treated with denosomin to investigate the mechanism of axonal growth facilitation. Key Results: Denosomin improved hind limb motor dysfunction and axonal growth, especially in the 5‐HT‐positive tracts across the scar and increased the density of astrocytes. Denosomin increased astrocyte proliferation, inhibited astrocytic death and increased the expression and secretion of vimentin in cultured astrocytes. Furthermore, vimentin increased axonal outgrowth in cultured neurons, even in the presence of inhibitory CSPG. Denosomin increased the number of vimentin‐expressing astrocytes inside glial scars of SCI mice, and 5‐HT‐positive axonal growth occurred in a vimentin‐associated manner. Conclusion and Implications: Denosomin increased the ratio of astrocytes that secrete vimentin as an axonal growth facilitator, which, we propose enhances axonal growth beyond the glial scar and promotes functional recovery in SCI mice. This study is the first to demonstrate this novel role of vimentin in SCI and drug‐mediated modification of the inhibitory property of reactive astrocytes.